A new model of selection in women`s handball - Srhoj, V.; Rogulj, N.; Zagorac, N.; Katic, R. (Collegium Antropologicum, 2006)
The aim of the study was to assess the basic motor abilities that determine top performance in women`s handball, and to identify test panel for primary selection at handball school. The study included 155 female attendants of the Split Handball School, mean age 12.5 years. Differences in the basic motor abilities between the subjects that developed into elite handball players after 7-year training process and those that abandoned handball for being unable to meet the competition criteria were evaluated by use of discriminative analysis. The former were found to have also been su erior initially in all variables analyzed, and in arm coordination, overall body coordination, throw and jump explosive strength, arm movement frequency and repetitive trunk strength in particular.Motor superiority based on the abilities of coordination, explosive strength and speed determines performance in women`s handball, qualifying these abilities as reliable selection criteria. Based on this study results, a new model of selection in women`s handball, with fine arm coordination as the major limiting factor of performance, has been proposed.